Asthma Self-Management: A Study in an Emergency Room of a Chest Hospital in Delhi, India - Kotwani, Anita (Dr. Zaheer-Ud-Din Babar, 2012)
Objectives: Poorly controlled asthma imposes a considerable burden and is a serious public health problem in the developing world. A key challenge for healthcare professionals is to help patients to engage in self-management behaviours with optimal adherence to appropriate treatment. The aim of the present study was to investigate the pattern of self-management in asthmatic patients enrolled as out-patients in a tertiary care referral public chest hospital, in Delhi, India. Methods: The study population was adult asthma patients (n=200) visiting the emergency room (December 2008-December 2009) of a chest hospital for asthma exacerbation. The data was collected through a questionnaire regarding the self-management of asthma. Results: Enrolled patients (64.0% female) were registered as asthma out-patients in the study hospital for a mean of 5.4±4.4 years. Patients visiting the emergency room (ER) and having an unscheduled visit to doctor at least twice in the previous 12 months were 86.5% and 91.0%. Patients were classified according to the disease severity as having intermittent (17.0%) or persistent (83.0%) asthma. Not all patients had metered dose inhalers at home. Only 2.0% of patients were prescribed peak flow meters and were keeping a diary of their readings. With one exception, patients did not have written action plans for treatment provided by doctor or health facility. No statistical difference was found in the pattern of self-management of patients having persistent or intermittent asthma. Conclusions: Findings revealed poor self-management of asthma and poor communication from doctors regarding self-management to the patients. Suitable actions and interventions are needed by health professionals to implement patient self-management asthma programme for optimum asthma control.